Gray platelet syndrome: Management of perioperative bleeding in redo cardiac surgery. Issue 2 (11th November 2019) - Carrascal, Yolanda; Laguna, Gregorio; Blanco, Miriam; Segura, Bárbara; Martínez‐Almeida, Iciar
Abstract: Gray platelet syndrome (GPS) is a rare (<1/1 000 000) and inherited platelet function disorder characterized by macrothrombocytopenia, α‐granule deficiency, and hemorrhages. Bleeding intensity does not correlate with platelet count nor with functional test results. We hereby describe the perioperative bleeding prevention and management of a patient with GPS requiring multiple redo cardiac surgeries.